Early identification of high-risk pregnancies in rural areas of Karnataka through maternal obstetric monitoring program - Janagam, Srujan G.; Kaniyampady, Smitha T.; Shetty, Anupama N. (International Journal Of Community Medicine And Public Health, 2020)
Maternal mortality rate (MMR) has been one of India’s key priority areas. Over the years. several national programs have addressed issues of accessibility and affordability of antenatal care. Major gaps in the system include shortage of trained human resource and technological infrastructure in providing essential diagnostic ante-natal care. High risk pregnancies (HRP) owing to various factors, account for 70-80% of maternal deaths. This case study describes the clinical and workflow process innovation in ante-natal care in Shorapur taluka, a rural region of Northern Karnataka. Maternal obstetric monitoring (MOM) through a defined protocol for high-risk pregnancy identification aided by ultrasound scans, was introduced at the sub-district hospital. In parallel, system strengthening was done through capacity building activities, installation of blood storage unit and provision of ultrasound services. The model demonstrates that process and technological innovations can be leveraged on to facilitate and make available specialist medical services in rural areas, which is key to identification and timely management of high-risk pregnancies.